2016
DOI: 10.1007/s12571-016-0582-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the value of diverse cropping systems under a new agricultural policy environment in Rwanda

Abstract: In Rwanda, farmers' traditional farming systems based on intercropping and varietal mixtures are designed to meet a variety of livelihood objectives and withstand risks associated with fluctuation in market and agro-climatic conditions. However, these mixed systems have been disappearing since 2008 when government mandated intensification strategies. In this paper we use a mixed methods approach to evaluate intercropping and sole cropping systems against farmers' criteria for success: yield, market value, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 74 publications
2
39
0
1
Order By: Relevance
“…Cereal crops common in Africa, such as maize, sorghum and millet have generally been bred for intensive traits such as shorter stature, early-maturation, pest and disease-resistance, input-responsiveness, and the production of multiple crops per year (Stoop et al, 2002). Aside from appreciation of yield, farmers' preferences vary across Sub-Saharan Africa and include non-market criteria such as environmental adaptation (to low-input systems and heterogeneous environments), plant architecture (Isaacs et al, 2016, vom Brocke et al, 2010, Voss, 1992), cooking qualities (Demont et al, 2012), and other consumption properties (Waldman et al, 2014, Ortega et al, 2016). As such we estimate farmer demand for perenniality in the context of perennial pigeon pea production in Malawi.…”
Section: Background On Perennial Cropsmentioning
confidence: 99%
“…Cereal crops common in Africa, such as maize, sorghum and millet have generally been bred for intensive traits such as shorter stature, early-maturation, pest and disease-resistance, input-responsiveness, and the production of multiple crops per year (Stoop et al, 2002). Aside from appreciation of yield, farmers' preferences vary across Sub-Saharan Africa and include non-market criteria such as environmental adaptation (to low-input systems and heterogeneous environments), plant architecture (Isaacs et al, 2016, vom Brocke et al, 2010, Voss, 1992), cooking qualities (Demont et al, 2012), and other consumption properties (Waldman et al, 2014, Ortega et al, 2016). As such we estimate farmer demand for perenniality in the context of perennial pigeon pea production in Malawi.…”
Section: Background On Perennial Cropsmentioning
confidence: 99%
“…In the northern region of the country, climbing beans were often relay intercropped and broadcast with maize or sorghum, whereas in the south bush beans were intercropped. In the past few years, agricultural policy in Rwanda has begun to discourage intercropping [21].…”
Section: Open Accessmentioning
confidence: 99%
“…In the SC, men and women mentioned yield with nearly the same frequency (25 and 27 %, respectively), while in the IC, men discussed yield 30 % of the time and women discussed it 24 % (Table 5). Yield was an essential attribute, and sole crop bean yields were often more than double that of intercrop yields, but parallel research to this revealed that farmers also valued other features of intercrops: the ability to harvest more than one crop from limited land, nutritional diversity, marketability of diverse products, community sharing, and reduced risk [21].…”
Section: Yield Themementioning
confidence: 99%
“…One concern in this method is reliability when Glenna et al Our measure of food security does not address other important measures of human well-being, such as nutritional quality and dietary diversity. Research indicates that smallholders who produce more diverse crops and who have access to local markets, as opposed to global markets, have better nutritional quality and dietary diversity (Jones et al 2014;Isaacs et al 2016). Although these issues are important, we chose this measure of food security to make the analysis more straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Isaacs et al (2016) found that a policy change in Rwanda to intensify commercial crop production reduced traditional cropping systems, which also led to a reduction in yield, market value, nutritional quality, and landuse efficiency. Although this Rwanda study is not directly linked to the World Bank structural adjustment policy, it demonstrates how a narrow emphasis on marketization and intensification can have detrimental impacts.…”
Section: Competing Perspectives On Agricultural Developmentmentioning
confidence: 99%